2020
DOI: 10.1111/bph.14993
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyperglycaemia and diabetes on acute myocardial ischaemia–reperfusion injury and cardioprotection by ischaemic conditioning protocols

Abstract: response of the diabetic heart to cardioprotective strategies e.g. IPC, IPost and RIC. Finally we highlight the effects of anti-hyperglycaemic agents on susceptibility to acute myocardial IRI and cardioprotection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 162 publications
(247 reference statements)
1
49
0
7
Order By: Relevance
“…Hyperglycaemia has been reported to contribute to tissue injury, particularly in heart disease 19,20 . Several signalling pathways have been analysed and targeted in cardiac fibrosis, senescence and ischaemia, on a dysmetabolic or cardiotoxic basis, including activation of the Stat3‐mediated pathway 21‐23 . In non‐diabetic mice undergoing ischaemia‐reperfusion injury, empagliflozin reduced myocardial infart size through STAT‐3 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperglycaemia has been reported to contribute to tissue injury, particularly in heart disease 19,20 . Several signalling pathways have been analysed and targeted in cardiac fibrosis, senescence and ischaemia, on a dysmetabolic or cardiotoxic basis, including activation of the Stat3‐mediated pathway 21‐23 . In non‐diabetic mice undergoing ischaemia‐reperfusion injury, empagliflozin reduced myocardial infart size through STAT‐3 24 .…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Several signalling pathways have been analysed and targeted in cardiac fibrosis, senescence and ischaemia, on a dysmetabolic or cardiotoxic basis, including activation of the Stat3-mediated pathway. [21][22][23] In non-diabetic mice F I G U R E 5 Effects of streptozotocin and empagliflozin on cardiac senescence-associated β-galactosidase activity in mice. Panels A-C, Senescence β-galactosidase (SA β-Gal) staining (magnification 5× and 40×) and quantitative evaluations (Panel D) in cardiac tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Andreadou et al (2020) summarize the existing data on animal models of hypercholesterolaemia (total, low density, and HDL abnormalities) and hypertriglyceridaemia used in ischaemia/reperfusion injury and cardioprotection and provide recommendations on animal models of translational value. Penna et al (2020) review the effect of diabetes and hyperglycaemia on cardioprotection. They overview the available animal models of diabetes and hyperglycaemia investigating acute myocardial ischaemia/reperfusion injury and cardioprotection.…”
Section: Figurementioning
confidence: 99%
“…review the effects of age and sex on the susceptibility and outcome of ischaemic heart disease Andreadou et al (2020). summarize the existing data on animal models of hypercholesterolaemia (total, low density, and HDL abnormalities) and hypertriglyceridaemia used in ischaemia/reperfusion injury and cardioprotection and provide recommendations on animal models of translational value Penna et al (2020). review the effect of diabetes and hyperglycaemia on cardioprotection.…”
mentioning
confidence: 99%
“…It is known that α 2 -adrenergic agonists such as xylazine or medetomidine acutely raise blood glucose to hyperglycemic values [ 3 , 4 ] in non-fasted animals, through inhibition of insulin release from pancreatic β cells. Numerous studies have demonstrated that hyperglycemia is strongly associated with increased infarct size [ 5 ]. We therefore postulate that the intravenously administered dapagliflozin quickly lowered the high blood glucose levels in these animals, thereby explaining the reduction in infarct size by dapagliflozin in this experimental condition.…”
mentioning
confidence: 99%